T Lymphocytes Influence the Mineralization Process of Bone - El Khassawna, Thaqif; Serra, Alessandro; Bucher, Christian H.; Petersen, Ansgar; Schlundt, Claudia; Könnecke, Ireen; Malhan, Deeksha; Wendler, Sebastian; Schell, Hanna; Volk, Hans-Dieter; Schmidt-Bleek, Katharina; Duda, Georg N. (Frontiers in Immunology, 2017)
Bone is a unique organ able to regenerate itself after injuries. This regeneration requires the local interplay between different biological systems such as inflammation and matrix formation. Structural reconstitution is initiated by an inflammatory response orchestrated by the host immune system. However, the individual role of T cells and B cells in regeneration and their relationship to bone tissue reconstitution remains unknown. Comparing bone and fracture healing in animals with and without mature T and B cells revealed the essential role of these immune cells in determining the tissue mineralization and thus the bone quality. Bone without mature T and B cells is stiffer when compared to wildtype bone thus lacking the elasticity that helps to absorb forces, thus preventing fractures. In depth analysis showed dysregulations in collagen deposition and osteoblast distribution upon lack of mature T and B cells. These changes in matrix deposition has been correlated with T cells rather than B cells within this study. This work presents, for the first time a direct link between immune cells and matrix formation during bone healing after fracture. It illustrates specifically the role of T cells in the collagen organization process and the lack thereof in the absence of T cells.